How Big Is Small? The Economic Effects of Access to Small Business Subsidies - J. David Brown; Matthew Denes; Ran Duchin; John Hackney (Institute of Labor Economics (IZA), 2024)
Industry size standards that determine eligibility for small business subsidies have vastly increased over the past decade. We exploit quasi-random variation in the implementation of size standard increases to study the effects on small firms, subsidy allocation, and industry outcomes using Census Bureau microdata. Following size standard increases, revenues decline for an industry's smallest firms, and they are less likely to survive. We link these effects to a reallocation of government procurement contracts from smaller to larger firms. Consequently, industries become more concentrated and growth declines. These findings highlight the broad economic effects of changing eligibility for small business subsidies.
Keywords: E24; G38; H25; H57; L25; 330; government subsidies; small firms; procurement